Use of antidepressant medication is associated with slower response to open-ended psychotherapy for depressed patients - Høstmælingen, Andreas; Nissen-Lie, Helene Amundsen; Monsen, Jon Trygve; Heinonen, Erkki; Wampold, Bruce E.; Czajkowski, Nikolai; Visted, Endre; Lau, Bjørn; Solbakken, Ole Andrè (Frontiers in Psychiatry, 2025)
ObjectiveDepressed patients often experience both symptomatic distress and interpersonal problems. Comorbid personality disorder (PD) has been shown to attenuate the benefits of psychotherapy. Also, antidepressant medication (ADM) may affect the response to psychotherapy. The objective of this study was to investigate changes in depressive symptoms and interpersonal problems for ADM users and non-medicated depressed patients during psychotherapy and follow-up, controlling for comorbid PD.MethodDepressive symptoms (SCL-90-R), and interpersonal problems (IIP-64) were assessed on 11 occasions for 166 depressed patients. ADM was used by 50.6% of the sample while 49.4% were unmedicated. Change during treatment and follow-up was assessed with multilevel modeling. We assessed whether ADM and PD predicted differences in symptom development.ResultsDepressive symptoms significantly reduced at a rate of.05 per month in treatment (p <.001), corresponding to an effect size of 1.35. Interpersonal problems significantly reduced at a rate of.02 per month during treatment (p <.001), corresponding to an effect size of.47. There was no significant difference between ADM users and nonmedicated patients at baseline. ADM users had nearly twice as long treatment duration than nonmedicated patients, and ADM users had lower rate of symptom reduction than nonmedicated patients for depressive symptoms and interpersonal problems. There were no differences in rates of change between patients with and without comorbid PD.ConclusionMedicated patients may experience less response to psychotherapy in terms of depressive symptoms and interpersonal problems compared to nonmedicated patients.